Hodgkin Lymphoma in Multifocal Unilateral Breast Cancer: Is it Simple Coincidence? - Al-Rashdi, Aya; Al Qassabi, Badryia; Al Ajmi, Radiya; Al Aghbari , Suad (International Journal of Innovative Research in Medical Science, 2021)
Breast cancer (BC) and malignant lymphoma (ML) each of them are considered as a common primary malignant disease worldwide. Synchronous occurrences of BC and ML are rare. We are presenting a case of a 34 year old patient with breast cancer and Hodgkin lymphoma detected in non-sentinel lymph node biopsy. This represents a rare case of coexistence of dual malignancies. We review the literature and discuss possible etiologies for these synchronous tumors.